Cerebral blood flow and glucose metabolism in long-term survivors of childhood acute lymphoblastic leukaemia - Kähkönen, M.; Harila-Saari, A.; Metsähonkala, L.; Korhonen, T.; Norvasuo-Heilä, M.-K.; Utriainen, T.; Ahonen, A.; Bergman, J.; Salmi, T.T.; Minn, H. (European journal of cancer (1990), 1999)
Central nervous system treatment for childhood acute lymphoblastic leukaemia (ALL) has been reported to cause changes in cerebral blood flow and glucose metabolism. Little is known about the association of these functional changes with neuropsychological defects and structural changes. The aim of the present study was to assess the relationship between changes in regional cerebral blood flow and glucose utilisation in long-term survivors of ALL, and the association of these functional abnormalities with neurocognitive and structural defects. 8 survivors of childhood ALL were studied with single photon emission tomography (SPECT) using Tc99m-ethyl cysteinate dimer (ECD) as tracer and with positron emission tomography (PET) using 18F-fluorodeoxyglucose (FDG) as tracer. 8 healthy controls also underwent FDG-PET. All subjects also underwent magnetic resonance imaging and neuropsychological assessment 5 years after cessation of the therapy. Focal cerebral blood flow abnormalities were found in ECD-SPECT in 5 of the 8 survivors. Glucose utilisation appeared normal in the corresponding regions. However, glucose utilisation was decreased in thalamus and cerebellum in the survivors of ALL as compared with healthy controls. 3 patients had severe and 5 patients mild neurocognitive difficulties. The changes in cerebral blood flow and FDG uptake did not correspond neuroanatomically with the neurocognitive defects. Focal defects in cerebral blood flow in long-term survivors of ALL are not associated with changes in local cerebral glucose utilisation. Neurocognitive difficulties are not consistently associated with either changes in cerebral blood flow or with decreased glucose utilisation. Therefore, based on the present set of studies FDG-PET and ECD-SPECT cannot yet be recommended for the evaluation of long-term neurocognitive defects associated with treatment of ALL.